Spastic secondary contractile patterns identified by FLIP panometry in symptomatic patients with unremarkable high‐resolution manometry. Issue 7 (24th January 2022) - Nguyen, Anh D.; Ellison, Ashton; Reddy, Chanakyaram A.; Mendoza, Roseann; Podgaetz, Eitan; Ward, Marc A.; Souza, Rhonda F.; Spechler, Stuart J.; Konda, Vani J.A.
Abstract: Background: Functional lumen imaging probe (FLIP) panometry can show spastic secondary contractile patterns of unclear significance in symptomatic patients who have no esophageal obstructive disorders, and no motility disorders on high‐resolution manometry (HRM). Methods: We retrospectively analyzed non‐obstructed, symptomatic patients with HRM findings of no motility disorder or ineffective esophageal motility (IEM) for whom spastic secondary contractile patterns identified by FLIP panometry were used to guide treatment. Symptoms were scored using the Brief Esophageal Dysphagia Questionnaire (BEDQ). Key Results: We identified ten symptomatic patients treated at our medical center who met inclusion criteria (seven women; mean age 56 years; eight no motility disorder, two IEM). On FLIP panometry, seven had spastic secondary contractions at 60 ml, two at 40 ml, and one at both 40 ml and 60 ml balloon volumes. Eight patients (80%) had improvement in BEDQ scores with therapies that targeted the spastic secondary contractile patterns identified by FLIP (five botulinum toxin injection, two Esoflip dilation, and one Heller myotomy). Interestingly, review of HRM tracings revealed that all patients had a novel HRM finding of mid‐vertical pressurization in at least 20% swallows, with seven exhibiting this finding in >50% of swallows. Conclusions: This case series demonstrates that treatments targeting spastic secondary contractions identified by FLIP panometry can result in symptomatic improvement in patients with no obstructive disorder and no diagnostic motility disorder on HRM. In such patients, we have identified the novel HRM finding of mid‐vertical pressurization, which might be the manometric manifestation of spasm limited to the mid‐esophagus. Abstract : Spastic secondary contractions on FLIP panometry (Figure A) and mid‐vertical pressurization on HRM (Figure B) have been found in symptomatic patients without a HRM diagnosis. Therapies targeting these findings can result in symptom improvement.